INDIVIDUALIZATION OF LEARNING AS PEDAGOGICAL THE PROBLEM IN THE CONTEXT IS PERSONAL FOCUSED EDUCATION - S.P. Bilokonnyy (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the history of individual approach in training and present-day state of given problem.